An abstract layered model for web inclusive distributed computing leading to enhancing GRIDSpace with Web 2.0 - Dillon, Tharam S.; Wu, Chen; Chang, Elizabeth (John Wiley & Sons Ltd, 2008)
Service Oriented Computing (SOC), Grid computing, and Web2.0 computing have increasingly received momentum in both research and industry. In this paper, we propose an abstract Web Inclusive Distributed Computing Model (WIDCOM) in order to analyse these three important distributed computing paradigms. We then advance the notion of software in existing Grid services as discussed in OGSA, which provides software middleware or wrappers for accessing hardware resources towards the notion that the resources provided can be hardware, software, or hybrid hardware/software. It also proposes an approach using the integration of Grid service, Semantic Grid, and Web2.0 to overcome some of the limitations of the existing Web services architecture which relies on having the Web version of the RPC mechanism and thus has difficulty in dealing with massive scale of user participation and communication across the Internet. The new approach produces a novel Grid architecture ? GRIDSpace.